ASSOCIATION OF BODY IMAGING, PHYSICAL ACTIVITY PATTERN, AND POSTPARTUM DEPRESSION AMONG WORKING MOTHERS: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background:A Working mother goes through a phase in her life in which she is expecting to take care of her child, look after her house responsibilities, and prove herself to be a perfect employee as well. These three things eventually led her to a cognitive condition a ‘Postpartum Depression’. Postpartum depression is an issue that faces negligence on a serious note, even though this issue is something that can not only destroy the mental health condition of a woman suffering from it, but also her partner and children. Being a working mother during the postpartum period plays a major role in increasing the chances of postpartum depression. Every mother wants herself to stay fit and healthy to balance both life at work and home perfectly. Inner self also wants to slay that ‘ideal’ body image for satisfaction. Plan to form a proper physical activity strategy and leniency from workplace highlight the importance of extensive postpartum support systems to ease the process of returning to work so that working mothers will be able to easily cope with their mental, physical, and emotional problems, eventually being able to alleviate all the challenges.Objective:The objective of this study is to investigate the association of body imaging, physical activity, and postpartum depression among working mothers.Methodology:This observational cross-sectional study has followed a non-probability convenient sampling that involved 169 working mothers aged between (21 to 45 years). Data collection procedure has been done via International Physical Activity Questionnaire (IPAQ), Body Shape Questionnaire (BSQ) and Edinburgh Postnatal Depression Scale (EPDS) questionnaires and the tests that has been performed includes chi square test, correlation regressions, cross-tab relations, descriptive statistics, reliability, multicollinearity, normality, homogeneity and diagnostic statistics.Result:The study, conducted among 169 working postpartum mothers in Karachi, investigated the interrelationships between depression (EPDS), physical activity (IPAQ), and body shape concerns (BSQ). According to EPDS results, 40.24% had no depression, 26.26% were borderline, and 35.5% were identified as having postnatal depression, most prevalent among women aged 26–30 and mothers with one child. IPAQ findings showed that 68.64% engaged in moderate activity, 20.12% in low activity, and only 11.24% in high activity levels. BSQ results revealed that 98.8% had mild body shape concerns, particularly among women aged 26–35 and those with one child. Descriptive statistics showed an average respondent age of 29.17 years and an average child count of 1.66. Correlation analysis indicated weak positive associations between depression and physical activity (4.00%) and depression and body shape concern (1.00%). EPDS items showed strong internal correlation (up to 75.1%), IPAQ items peaked at 54.9%, and BSQ correlations ranged up to 32.5% (with a minimum of -10.0%). Chi-square tests confirmed significant associations among key variables, rejecting null hypotheses.Conclusion:This study highlights the psychological vulnerabilities faced by working mothers in the postpartum period, emphasizing the significant, though statistically weak, interplay between depressive symptoms, physical inactivity, and body dissatisfaction. Despite high mild body shape concerns and moderate activity levels in the sample, a considerable proportion of mothers reported postnatal depression. The results stress the importance of promoting physical activity and positive body image to improve mental well-being in postpartum women. Moreover, the research calls for workplace and societal interventions to support maternal mental health, especially during the critical return-to-work transition. Although the findings are informative, the study's generalizability is limited by its cross-sectional design, non-random sampling, and exclusion of certain groups. Nonetheless, the study contributes valuable data for future culturally sensitive research and policy formulation.